Motivation, challenges and realities of volunteer community cardiac arrest response: a qualitative study of ‘lay’ community first responders - Barry, Tomás (BMJ Open, 2019)
OBJECTIVES: To explore the reasons why lay community first responders (CFRs) volunteer to participate in out-of-hospital cardiac arrest response and the realities of their experience in providing this service to the community. DESIGN: A qualitative study, using in-depth semistructured interviews that were recorded and transcribed. Thematic analysis was undertaken and credibility checks conducted. SETTING: Nine geographically varied lay CFR schemes throughout Ireland. PARTICIPANTS: Twelve experienced CFRs. RESULTS: CFRs were motivated to participate based on a variety of factors. These included altruistic, social and pre-existing emergency care interest. A proportion of CFRs may volunteer because of experience of cardiac arrest or illness in a relative. Sophisticated structures and complex care appear to underpin CFR involvement in out-of-hospital cardiac arrest. Strategic and organisational issues, multifaceted cardiac arrest care and the psychosocial impact of participation were considered. CONCLUSIONS: Health systems that facilitate CFR out-of-hospital cardiac arrest response should consider a variety of relevant issues. These issues include the suitability of those that volunteer, complexities of resuscitation/end-of-life care, responder psychological welfare as well as CFRs’ core role of providing early basic life support and defibrillation in the community.